VOCATIONAL SKILL LEARNING DEVELOPMENT FOR INTELLECTUAL DISABILITY CHILDREN (Proceedings of International Conference on Special Education, 2019)
This research was motivated by ability problems in vocational learning for intellectual disability children not optimal yet and ineffective in organizimh groups vocational training that held by a few foundation for managing intellectual disability education in Bandung. Based on these circumstances this research aims to: 1) obtain an overview of the objective conditions of vocational learning for intellectual disability children 2) Concepts and theories that are used as referenced in the implementation of this research, comprise: the nature of vocational learning in SLB, the reality in the field that not all of intelectual disability children could get formal education through SLB because of various obstacle such as, distant school distance from their home, limited costs, low parental awareness, also low public awareness. The result of research indicates: the existence of vocational learning not optimal. The conclusion of this research is that vocational skill learning development for intelectual disability children can be said effective in increasing wok ability, as knowledge, skill. Recommendation for research results is vocational development for intelectual disability children and can direct them to get a job as provision of their life